Abordagem da produção do cuidado no processo de formação da enfermeira para o sistema único de saúde - Assunção, Lara Rios Alencar (2018)
The training of nurses has been widely discussed in order to enable the transformation of care practices so that the nurse learn the dynamics of the production of integral health care as a strategy to intervene in the health-disease process in a critical, reflective and creative way in the search for the guarantee of the execution of the principles and guidelines recommended by the Unified Health System (SUS). The study has as the main objective to understand the approach of the production of integral care as the center line of the nurses' training process for the Unified Health System in a nursing undergraduate course and it has as its specific objective to discuss the pedagogical practices implemented in view to the production of care in the process of training the nurse. It is a study with a qualitative approach, it used the action-research method, having as participants 10 teachers who possess the curricular components Nursing Management in Health Services (8th semester), Supervised Internship I (9th semester) and Supervised Internship II (10th semester) and 12 students of the curricular component Supervised Internship II of the undergraduate course in Nursing at the State University of Feira de Santana. There were used as data collection techniques group meetings, semi-structured interviews and documentary analysis. The data were organized and interpreted through thematic content analysis. The study shows that the challenge of achieving the production of integral care in the training of nurses requires training aimed at acquiring skills that aim at quality care, develop the capacity for critical analysis, problematize current practices, and establish strategies of teaching and learning that favor the exchange of knowledge, dialogue and interdisciplinarity, that is, training for citizenship. To develop the capacity to learn and teach, students and teachers, to guarantee a humanized, integral and quality care. The reflections raised in the research revealed the need for changes in the teaching-learning process. In this sense, it is proposed the discussion and reflection on the need to make teaching and learning more flexible, applying innovative, problematizing and constructive pedagogical practices that promote students' autonomy, recognizing that the process of learning is continuous and pervades our whole existence